2010
DOI: 10.31729/jnma.145
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology and Antibiotic Susceptibility Pattern of Peitonsillar Abscess

Abstract: INTRODUCTION: Peritonsillar abscess is a common complication of acute tonsillitis. Its management consists of aspiration or surgical drainage followed by appropriate antibiotics. Appropriate antibiotic treatment depends on the common organisms associated with infection and their antibioticsensitivity pattern in local scenario. METHODS: Pus samples aspirated from diagnosed cases of peritonsillar abscess and submitted for culture and sensitivity in last two years were included in this study. Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…Patients usually present with severe throat pain, fever, drooling, foul breath, trismus, neck swelling, and altered voice resonance. Microbiological findings for peritonsillar abscesses include both aerobic and anaerobic components [3,[5][6][7][8]. The aerobic bacterium Streptococcus pyogenes is isolated in nearly a third of cases [1].…”
Section: Introductionmentioning
confidence: 99%
“…Patients usually present with severe throat pain, fever, drooling, foul breath, trismus, neck swelling, and altered voice resonance. Microbiological findings for peritonsillar abscesses include both aerobic and anaerobic components [3,[5][6][7][8]. The aerobic bacterium Streptococcus pyogenes is isolated in nearly a third of cases [1].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 There is debate as to how common penicillin resistance is in peritonsillar abscesses, ranging from 0% to 68%. A 37.5% penicillin resistance rate in Staphylococcus is similar to what is reported in the literature, with a range of 0% to 52%.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 There is debate as to how common penicillin resistance is in peritonsillar abscesses, ranging from 0% to 68%. [2][3][4] The presence of clindamycin and erythromycin resistance in Streptococcus and Staphylococcus seen in this study is also demonstrated by prior studies. 2 The majority of penicillin resistance reported appears to be due to β-lactamase production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also found similar results with Staphylococcal specimens showing high levels of anti-microbial resistance, and Streptococcal species being relatively susceptible to first line antibiotics. (10) Another interesting aspect of drug susceptibility testing was that 80% of the Pseudomonas samples were resistant to third generation cephalosporins, indicating a possible presence of Extended Spectrum Beta Lactamase (ESBL). Phenotyping and Polymerase Chain Reaction (PCR) would have been the obvious choice of looking for ESBL, but it was not done as institutional facilities were not available.…”
mentioning
confidence: 99%